Induction of Antinuclear Antibodies by De Novo Autoimmune Hepatitis Regulates Alloimmune Responses in Rat Liver Transplantation - Toshiaki Nakano; Shigeru Goto; Chia-Yun Lai; Li-Wen Hsu; Hui-Peng Tseng; Kuang-Den Chen; King-Wah Chiu; Chih-Chi Wang; Yu-Fan Cheng; Chao-Long Chen (Clinical and Developmental Immunology, 2013)
Concanavalin A (Con A) is a lectin originating from the jack-bean and well known for its ability to stimulate T cells and induce autoimmune hepatitis. We previously demonstrated the induction of immunosuppressive antinuclear autoantibody in the course of Con A-induced transient autoimmune hepatitis. This study aimed to clarify the effects of Con A-induced hepatitis on liver allograft rejection and acceptance. In this study, we observed the unique phenomenon that the induction of transient de novo autoimmune hepatitis by Con A injection paradoxically overcomes the rejection without any immunosuppressive drug and exhibits significantly prolonged survival after orthotopic liver transplantation (OLT). Significantly increased titers of anti-nuclear Abs against histone H1 and high-mobility group box 1 (HMGB1) and reduced donor specific alloantibody response were observed in Con A-injected recipients. Induction of Foxp3 and IL-10 in OLT livers of Con A-injected recipients suggested the involvement of regulatory T cells in this unique phenomenon. Our present data suggest the significance of autoimmune responses against nuclear histone H1 and HMGB1 for competing allogeneic immune responses, resulting in the acceptance of liver allografts in experimental liver transplantation.